Synthesis of High-Quality Large-Area Homogenous 1T' MoTe2 from Chemical Vapor Deposition - Zhou, Lin (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.